Enhancement of Seawater NaCl Concentration Using Spray-Assisted Evaporation and Ion Exchange Pretreatment - Muhammad Dillah Sudaiz; Angesti Hayunendyah; Caecilia Pujiastuti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study investigates the enhancement of seawater NaCl concentration using a combination of ion exchange pretreatment and spray-assisted heating as an alternative method for a more efficient and sustainable salt concentration process. The novelty of this study lies in the utilization of Dowex cation and anion exchange resin pretreatment prior to the spray heating process to reduce impurity ions that may affect the NaCl concentration process. This study aims to analyze the effect of nozzle-to-heating plate distance variations (16, 18, 20, 22, and 24 cm) and spraying flow rates (25, 30, 35, 40, 45, 60, and 70 L/h) on the increase of seawater %Brix values. Before the concentration process, seawater was pretreated using Dowex cation and anion exchange resins for 25 minutes to reduce impurity ion content. The results showed that the optimum operating condition was achieved at a nozzle distance of 16 cm and a spraying flow rate of 45 L/h for 5 hours, resulting in a maximum concentration of 15 %Brix. The concentration enhancement was also indicated by the darker color of the solution due to the increase in dissolved solids content. Scientifically, this study demonstrates that ion exchange pretreatment followed by spray heating can improve the effectiveness of seawater concentration. Furthermore, this method has the potential to be applied in the salt industry as a more energy-efficient alternative technology, supporting the improvement of national salt raw material quality and contributing to the development of more sustainable salt production processes. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action